Effect of nano silica on durability properties of concretes containing recycled coarse aggregates - Shaikh, Faiz; Odoh, H. (Conference committee., 2014)
This paper presents the effect of nano silica (NS) on durability properties of concretes containing recycled coarse aggregates (RCA). The RCA is sourced from local construction and demolition (C&D) wastes. Seven series of concretes are considered in this study. The first series is the control series which contains all natural aggregates and no NS. In the second and third series, 25% and 50% (by wt.) natural coarse aggregate are replaced by RCA, respectively. The effects of NS on concretes containing RCA are evaluated in rest of the series. In fourth and fifth series, 1% and 2% (by wt.) NS are added in concrete containing 25% RCA, respectively. The sixth and seventh series are similar to fourth and fifth series in every aspect except the RCA content of 50%. Durability properties, such as sorptivity, volume of permeable voids and chloride penetration of above concretes are evaluated after 7 and 28 days of water curing. Results show that the addition of NS significantly improves the above durability properties of concretes containing 25% and 50% RCA.